Invasive micropapillary type male breast cancer: a case report - Acar, Muhammet Sefa; Şimşek, Sercan; Urfalı, Furkan Ertürk; Korkmaz, Mehmet (The European Research Journal, 2024)
Male breast cancer is rarely seen and peaks at the age of 71. Hyperestrogenism, gonadal dysfunction, obesity, and alcohol are among the risk factors for male breast cancer. In hereditary cases, BRCA2 mutation is often observed. The most common symptom is a painless mass that is palpable behind the nipple. Most male breast cancers are ductal carcinomas (81%), papillary carcinomas (13%), and mucinous carcinomas (6%). The invasive micropapillary carcinoma of the breast is important due to its high rate of lymphnode metastasis, recurrence, and distant metastasis. Mortality is 50% higher in men with lymphnode involvement compared to non-involved cases. Furthermore, as the number of affected lymphnodes increases, the prognos is worsens. In this study, we examined a case of invasive micropapillary type male breast cancer with clinical presentation as a palpable mass, lymphnode involvement, and aimed to highlight the radiological considerations that need attention.